The role of anti-vascular endothelial growth factor (anti-VEGF) in the management of proliferative diabetic retinopathy - Zhao, Yue; Singh, Rishi P (Drugs in Context, 2018)
Diabetes is a major cause of visual impairment among working-age adults in the United States. The proliferative form of diabetic retinopathy is associated with severe vision loss (acuity <5/200). The standard treatment in proliferative diabetic retinopathy (PDR) is panretinal photocoagulation (PRP), which is effective but has established side effects such as peripheral visual-field constraints. Vascular endothelial growth factor (VEGF) is thought to drive the process of vascular proliferation. Drugs targeting VEGF (anti-VEGF) have been studied extensively in diabetic macular edema (DME), and results have shown that diabetic retinopathy regresses with anti-VEGF treatment. Recent studies show that anti-VEGF is not inferior to PRP for PDR while treatment is maintained, though recurrence rate when anti-VEGF treatment is stopped is unclear. In vitreous hemorrhage where PRP cannot be performed, use of anti-VEGF medications can treat underlying PDR and delay or reduce need for vitrectomy. Limitations of anti-VEGF treatment, however, require careful patient selection and monitoring. This review discusses recent clinical trials and guidelines for anti-VEGF use in PDR.